A study on the presence, role and significance of perchloric-acid soluble protein (PSP) in blast cells of acute leukemic patients . - Mat, Mat Ludin Che; Nordin, Hasenan; Wan Mohamed, Wan Maziah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2006)
The purpose of this study was to detect the presence of perchloric-acid-soluble protein (PSP) in blast cells of acute leukemic patients and to conduct in-vitro study on the possibility of blast cells be proliferated into matured cells when treated with PSP. Samples from acute myeloblastic leukemic (AML) patients and monocytes from healthy donor were used as a test subject. The small amount of perchloric-acid-soluble 14.5 kDa protein (PSP) was isolated from monocytes of healthy donor by a combination of trichloroacetic acid extraction, preparative electrophoresis and CM-Sephadex chromatography. However, this protein was not found in blast cells of AML patients. The 14.5 kDa protein showed a strong cross-reactivity when tested with PSP antibody suggesting a close similarity to p14.5 PSP found in mononuclear phagocytes of human. However in our in-vitro study on the proliferation of blast cells of AML samples after treated with PSP showed some reaction, but no significant results. Thus, we believed that the amount of PSP used in this study was too small which was not enough to play a significant role in cell development and maturity.